2018
DOI: 10.1002/psp4.12276
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Anemia Trial: An Assessment of Model‐Based In Silico Clinical Trials of Anemia Treatment Algorithms in Patients With Hemodialysis

Abstract: In silico approaches have been proposed as a novel strategy to increase the repertoire of clinical trial designs. Realistic simulations of clinical trials can provide valuable information regarding safety and limitations of treatment protocols and have been shown to assist in the cost‐effective planning of clinical studies. In this report, we present a blueprint for the stepwise integration of internal, external, and ecological validity considerations in virtual clinical trials (VCTs). We exemplify this approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…A key idea is the shift from real-world clinical trial testing a single treatment option on many, mostly unselected, patients to first test in silico several treatment options, both approved or repurposed, for each individual patient. Importantly, mathematical models can also optimize the dosage and scheduling of the selected treatment [141, 162, 164166].…”
Section: Discussionmentioning
confidence: 99%
“…A key idea is the shift from real-world clinical trial testing a single treatment option on many, mostly unselected, patients to first test in silico several treatment options, both approved or repurposed, for each individual patient. Importantly, mathematical models can also optimize the dosage and scheduling of the selected treatment [141, 162, 164166].…”
Section: Discussionmentioning
confidence: 99%
“…Individual patients were represented by a patientspecific parameter set (RBC life span, ESA half-life, endogenous Epo levels, and effective parameters accounting for the ESA's effect on erythroid progenitor apoptosis and maturation velocity) capturing their erythropoiesis-related physiology (Fuertinger FIGURE 5 | Estimation of physiological parameters in a HD patient population using a physiology-based model of erythropoiesis (Fuertinger et al, 2013). Shown are relative frequencies of estimated RBC life span (left) and endogenous Epo levels (right) obtained from patient-individual model adaptations to hemoglobin and ESA administration data of 6,659 HD patients, resulting in a virtual patient population (Fuertinger et al, 2018b) (see the main text for details).…”
Section: Relation Between Rbc Life Span and Epo Requirement: Insightsmentioning
confidence: 99%
“…10.2 U/L, 21.1 U/L). The relative frequencies of estimated RBC life spans and endogenous Epo levels among the population of virtual patients reported in Fuertinger et al (2018b) are shown in Figure 5.…”
Section: Relation Between Rbc Life Span and Epo Requirement: Insightsmentioning
confidence: 99%
See 2 more Smart Citations